Test cell for electrical double-layer capacitor. (2020) - Manyam, Jedsada
Abstract: A Swagelok union was modified to be a 2-electrode test cell for an electrical double layer capacitor (EDLC). The modified test cell was capable of determining and reproducing pressure applied on electrodes, thus it provided consistency for every cell assemblies. Galvanostatic charge-discharge measurements were conducted to evaluate performance of the modified test cell. The results showed that standard deviations of both specific capacitance and internal resistance of capacitors in the modified test cell were approximately 4-time less than those in a conventional Swagelok test cell.